Окремі аспекти формування і розвитку системи контролінгу на підприємстві - Шиян, Наталія Іванівна; Ковальова, О. В. (Одеський національний економічний університет, 2022)
Узагальнено підходи щодо визначення сутності поняття «контролінг», визначено особливості розуміння цієї категорії в окремих країнах світу. Систематизовано і розкрито сутність сучасних методів контролінгу витрат (загальнонаукові та специфічні), які використовуються підприємствами для підвищення ефективності прийняття управлінських рішень у сучасних умовах їх розвитку. Із використанням показників площі сільськогосподарських угідь та величини адміністративних витрат на 1 га сільськогосподарських угідь у сільськогосподарських підприємствах Харківської області у 2020 р. обґрунтована необхідність впровадження служби контролінгу на підприємствах, площа сільськогосподарських угідь яких перевищує 6500 га.

The article demonstrates the necessity of considering the problem of developing a controlling system at the enterprise level. Approaches to defining the essence of the concept of "controlling" are systematized, as well as the peculiarities of understanding the definition in some countries, in particular, the existence of various aspects of their understanding and application at the level of global economic entities, and specifically in Ukraine. The existence of a controlling service at the enterprise level, or the inclusion of its specialists in the financial service of the enterprise, are deemed as necessary in order to make informed decisions aimed at achieving the strategic goals of the enterprise. The essence of modern methods of cost control (general and specific), which are used by enterprises to increase the efficiency of management decisions in modern conditions of their development, is systematized and explored. Using statistical data of agricultural enterprises within the Kharkiv region for 2020, in particular, indicators of agricultural land area and administrative costs per 1 ha of agricultural land and, using the equation of the third order parabola, extreme points are determined – that is, their maximum and minimum values. The obtained results served as a basis for the conclusion on the need to introduce a controlling service within enterprises with an area of agricultural land exceeding 6,500 hectares.
Aspects of formation and development of the control system within the enterprises
Keywords: управління; витрати; економіка; фінанси; стратегічний контролінг; оперативний контролінг; strategic controlling; management; expenses; operational controlling; administrative expenses